ARNAWLÍ MEKTEPLERDE ANA TILIN OQÍTÍWDA ZAMANAGÒY TEXNOLOGIYALARDAN PAYDALANÍWDÍŃ ÀHMIYETI - Tajimuratova, K.; Tajimuratov, A. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of using innovative educational technologies in teaching process at specialized boarding schools. Nowadays, the importance of organizing classes with the use of modern pedagogical technologies is especially remarkable in primary education. The effective use of this kind of technologies will help achieve the desired results in the education of harmonically-developed generation.